Standardization of the drying process of halymenia durvillaei - Guillermo, Joy Veronica L.
ABSTRACT The drying process of Halymenia durvillaei was optimized and standardized in this study. Optimization of the pretreatment and drying temperature revealed that soaking the seaweed in 10% IPA for 20 minutes prior to drying at 55°C produced a product that is closest to the color value of the fresh Halymenia durvillaei, when rehydrated. The color analysis in the standardization phase of the optimized process showed significant differences among production runs for HUnter L (Pr>F= 0.0001), a (Pr>F= 0.0097) and b (Pr>F= 0.0436) values. However, the Consumer Acceptance score exhibited no significant detectable difference for all attributes (P>0.05). Hence, based on the Consumer Acceptance Test, the drying process can be said to be standardized as perceived by the panelists. The microbial load of samples from all production runs were within the acceptable range. Thus, the product can be considered safe for human consumption.